Increase in Congenital Toxoplasmosis During the COVID-19 Pandemic in the US - Despina G. Contopoulos-Ioannidis; Valerie Bonetti; Jose G. Montoya (Pathogens, 2024)
During the COVID-19 pandemic, prenatal care services were disrupted. We analyzed the trajectory slopes of cases of congenital toxoplasmosis (CT) and acute toxoplasmosis during pregnancy from 2019 to 2022 (to reflect the cases during the pandemic years 2020–2022) vs. 2000 to 2019, using data from the Remington Laboratory, the National Reference Center for Toxoplasmosis in the US. During the pandemic, there was a statistically significant upward trajectory in the yearly number of CT cases. Monitoring of this trend is needed.